Agreement between gastrointestinal panel testing and standard microbiology methods for detecting pathogens in suspected infectious gastroenteritis: Test evaluation and meta-analysis in the absence of a reference standard. - Karoline Freeman; Alexander Tsertsvadze; Sian Taylor-Phillips; Noel McCarthy; Hema Mistry; Rohini Manuel; James Mason (PLoS ONE)
Objective Multiplex gastrointestinal pathogen panel (GPP) tests simultaneously identify bacterial, viral and parasitic pathogens from the stool samples of patients with suspected infectious gastroenteritis presenting in hospital or the community. We undertook a systematic review to compare the accuracy of GPP tests with standard microbiology techniques. Review methods Searches in Medline, Embase, Web of Science and the Cochrane library were undertaken from inception to January 2016. Eligible studies compared GPP tests with standard microbiology techniques in patients with suspected gastroenteritis. Quality assessment of included studies used tailored QUADAS-2. In the absence of a reference standard we analysed test performance taking GPP tests and standard microbiology techniques in turn as the benchmark test, using random effects meta-analysis of proportions. Results No study provided an adequate reference standard with which to compare the test accuracy of GPP and conventional tests. Ten studies informed a meta-analysis of positive and negative agreement. Positive agreement across all pathogens was 0.93 (95% CI 0.90 to 0.96) when conventional methods were the benchmark and 0.68 (95% CI: 0.58 to 0.77) when GPP provided the benchmark. Negative agreement was high in both instances due to the high proportion of negative cases. GPP testing produced a greater number of pathogen-positive findings than conventional testing. It is unclear whether these additional 'positives' are clinically important. Conclusions GPP testing has the potential to simplify testing and accelerate reporting when compared to conventional microbiology methods. However the impact of GPP testing upon the management, treatment and outcome of patients is poorly understood and further studies are needed to evaluate the health economic impact of GPP testing compared with standard methods. The review protocol is registered with PROSPERO as CRD42016033320.